2020
DOI: 10.1111/jcmm.15340
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGFβ‐activated protein kinase 1 ameliorates myocardial ischaemia/reperfusion injury via endoplasmic reticulum stress suppression

Abstract: Transforming growth factor β‐activated protein kinase 1 (TAK1) involves in various biological responses and is a key regulator of cell death. However, the role of TAK1 on acute myocardial ischaemia/reperfusion (MI/R) injury is unknown. We observed that TAK1 activation increased significantly after MI/R and hypoxia/reoxygenation (H/R), and we hypothesized that TAK1 has an important role in MI/R injury. Mice (TAK1 inhibiting by 5Z‐7‐oxozeaenol or silencing by AAV9 vector) were exposed to MI/R injury. Primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The method was previously described by our group. 11 The macrophages were RAW264.7. Mouse coronary endothelial cells were purchased from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…The method was previously described by our group. 11 The macrophages were RAW264.7. Mouse coronary endothelial cells were purchased from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis induced by endoplasmic reticulum stress. RI, impaired autopha/RI, deficiency of glucose and nutrient supply, ATP depletion, ROS accumulation, and destruction of Ca 2+ homoeostasis interfere with endoplasmic reticulum (ER) function, causing unfolded protein response with unfolded/misfolded protein accumulation, the condition referred to as ER stress [ 87 , 88 ]. Numerous studies have indicated the association between ER stress and cardiomyocyte apoptosis [ 89 ].…”
Section: Pathways Through Which Oxidative Stress Causes Myocardial Reperfusion Injurymentioning
confidence: 99%
“…Numerous studies have indicated the association between ER stress and cardiomyocyte apoptosis [ 89 ]. Prolonged and/or excessive ER stress has been reported to induce ER-related apoptosis with increased expression of CCAAT/enhancer-binding protein homologous protein (CHOP) and the activation of caspase-12 [ 87 , 90 ]. Simultaneously, ER stress was thought to disrupt the redox balance, causing ROS accumulation and mitochondria dysfunction, finally aggravating cardiomyocyte apoptosis [ 90 ].…”
Section: Pathways Through Which Oxidative Stress Causes Myocardial Reperfusion Injurymentioning
confidence: 99%
“…Recent studies showed that multiple mechanisms are involved during the process of myocardial I/R injury, such as inflammation, apoptosis, intracellular calcium overload, endothelial dysfunction, reactive oxygen species, and endoplasmic reticulum stress (ERS). [3][4][5][6][7][8] Under physiological conditions, the endoplasmic reticulum serves many essential roles in cell function, including protein synthesis, protein folding, calcium homoeostasis, and lipid metabolism. 8,9 Under a stress condition such as the myocardial I/R process, the endoplasmic reticulum homoeostasis is disrupted, and unfolded or misfolded proteins accumulates, leading to the prolonged unfolded protein response (UPR) during ERS.…”
Section: Introductionmentioning
confidence: 99%